Parasitic Disease and COVID-19 Syndemics in Indonesia: Biomedical Aspects - Trasia, Reqgi First (Jurnal Medis Islam Internasional, 2023)
Background: Syndemics happened while two or more coinfections have dangerous interaction and lead to a harmful outcome than for either single infection. In Indonesia, during COVID-19 pandemic, it has deal with a doble burden presume to neglected tropical disese (NTD) control. Parasitic disease as a part of NTD must be a concern in Indonesia along pandemc. There are still few articles that review the biomedical aspects of co-infection COVID-19 with parasitic diseases in Indonesia, whereas an understanding of biomedical aspects can encourage knowledge about pathogenesis which will make an earlier diagnosis. Results: This review summarize how parasites may serve as protective agents or risk factors in pandemic and, vice versa, how the COVID-19 may disturb the prevention and misdiagnosis of parasitic disease in Indonesia. Co-infection COVID-19 with malaria increass the burden of severe clinical manifestations and poor prognosis due to exaggerated proinflammatory response. Coinfection triggers TNF and IL-6 to activate coagulation cascade leading to micro-thrombosis and coagulopathy. Besides, helminthiasis causes vary configuration of immune-modulation, thereby lowering susceptibility to other infections and tolerating COVID-19 better. They modify Th2 respons to limit pro-inflammatory cytokines, such as IL-6 which is observed in severe cases of COVID-19. T-cell hypoactivation in SARS-CoV-2 and W.bancrofti will cause  relatively mild manifestation of COVID-19. Conclusions: In parasite infection, the IL-4 may elevate and induce shadow memory CD8+ T-cell (TVM cell) for CD8 response rapidly agains virus. It control human IL-4 or IL-10 that leads to the maturation of Th2 cells and down-regulation of the inflamation respons of IFN-g, IL-17 and TNF-a. These mechanisms allow us to blockade the cytokines storms observed in COVID-19 cases.